CURRENT VIEWS ON ANTITHROMBOTIC THERAPY IN NON-CARDIOEMBOLIC STROKE - A. V. Fonyakin; L. A. Geraskina («REMEDIUM GROUP» Ltd., 2017)
The article describes current views on the role of antiplatelet therapy in the secondary prevention of cardiovascular diseases in patients after non-cardioembolic ischemic stroke or transient ischemic attack (TIA). Based on the findings of evidence-based medicine, an analytical description of all platelet antiaggregants that have been clinically tested worldwide is presented. The benefits and shortcomings of each agent both in mono- and combination therapy are demonstrated. The novel ideas about rationality of the combination antiplatelet therapy with clopidogrel and acetylsalicylic acid in the first 24 hours lasting up to 90 days in patients with small ischemic stroke or TIA are highlighted. The effectiveness and safety of new platelet antiaggregants are analyzed. The key principles that guide the choice of antiplatelet agents in patients after ischemic non-car-dioembolic stroke are outlined.